MUSEUM KISAH KESULTANAN PASIR KABUPATEN PASER DI KALIMANTAN TIMUR - Mardiati, Mardiati; Oktaviana, Anna (UNIVERSITAS LAMBUNG MANGKURAT, 2023)
The Museum of the Story Sultanate of Pasir Regency in East Kalimantan is a museum that takes the historical history of the story of the Sultanate of Pasir events so that people and visitors know how the story of the Sultanate of Pasir events and also know and remember the sultans who have existed..The design of this. story museum space.uses the.concept of sequence with the problem seeking method as a problem solver. The concept of sequence refers to the sequence of spaces that ultimately the circulation of space can be.in line with the.story of the Sultanate of Pasir. In order for visitors to understand what is displayed in the exhibition display space, it.is necessary.to have a sense.of space character.and.visualization so that the sequence to be achieved can be an experience and insight for visitors.